Effects of Inclined Plate in a Channel to Control Melting of PCM in a Body Inserted on the Bottom Wall - Öztop, Hakan Fehmi; Bakir, E.; Selimefendigil, Fatih; Gur, M.; Cosanay, H. (Springer, 2023)
A two-dimensional time-dependent computational analysis was carried out to examine the effects of inclined plate on melting time of Phase Change Material (PCM) filled square block on the bottom wall of a channel. Solution of the governing equations are performed by using finite volume method. The RT25HC material is chosen as PCM. The study is done for different parameters of inclination angle of the plate and Reynolds number. It is observed that the inclined plate can be used to control of melting time of PCM in a block as well as flow field and temperature distribution in the channel. Using of acceleration angle as theta=110 degrees accelerates the melting time of PCM inside the block. Thus, mass fraction rate increases 4 times with application of inclined thin plate.
Keywords: PCM; Melting; Heat Transfer Enhancement; Energy Storage; CFD